Neurological Disorder Brain Model: A Lesson from Marine Worms (Annelida: Polychaeta) - Nazri, Mohd Ulul Ilmie Ahmad (Malays J Med Sci, 2019)
The incidence of neurodegenerative diseases is directly proportional to age. The prevalence of non-communicable diseases, for example, Alzheimer’s and Parkinson’s, is expected to rise in the coming years. Understanding the etiopathology of these diseases is a crucial step that needs to be taken to develop drugs for their treatment. Animal models are being increasingly used to expand the knowledge and understanding on neurodegenerative diseases. Marine worms, known as polychaetes (phylum Annelida), which are abundantly and frequently found in benthic environments, possess a simple yet complete nervous system (including a true brain that is centralised and specialised) compared to other annelids. Hence, polychaetes can potentially be the next candidate for a nerve disease model. The ability to activate the entire nervous system regeneration (NSR) is among the remarkable features of many polychaetes species. However, the information on NSR in polychaetes and how it can potentially model neurodegenerative diseases in humans is still lacking. By exploring such studies, we may eventually be able to circumvent the developmental constraints that limit NSR in the human nervous system. This article is intended to briefly review responsible mechanisms and signalling pathways of NSR in marine polychaetes and to make a comparison with other established models of neurodegenerative disease.